Data supporting the cardiac mitochondria calcium handling in female normotensive and spontaneously hypertensive rats - Ciocci Pardo, Alejandro (2016)
In association with the published article "Mitochondrial calcium handling in normotensive and spontaneously hypertensive rats: correlation with systolic blood pressure levels", this data article contains information about calcium handling of cardiac mitochondria isolated from female of both rats strains (WKY and SHR). Dataset of mitochondrial permeability transition pore (mPTP) resistance to opening Ca2+-mediated, Ca2+ retention capacity (CRC), time constants and mitochondrial membrane potential (ΔΨm) are showed.